Mapping And Analysis of Environmental Risk Factors Leptospirosis Incidence Based Geographic Information System (GIS) In Sampang Regency - Annisa Rahim; Ririh Yudhastuti (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: One  of the  zoonosis in Indonesia is leptospirosis. Leptospirosis is caused due  to infection  of bacteria Leptospira. There  were  107 cases and  9 deaths due  to leptospirosis in Sampang. The  incidence of leptospirosis in Sampang was an outbreak. The purpose of this study  was to map the distribution  of leptospirosis cases in Sampang in 2013 and to analyze environmental risk factors of leptospirosis cases (rainfall, altitude, and the presence of flood). This study  was an observational-descriptive study  and used cross-sectional study  design. The unit of analysis  of the study was administrative  regions  based on the districts.  There was patients  of leptospirosis in 4 districts in Sampang regency, there are Sampang district, Camplong district Robatal district and Omben district. The highest incidence of leptospirosis in Sampang regency was occured in Sampang district with rainfall more than 177.6 mm,  altitude less  than 47mdpl, and had experienced flooding.  Mapping  the incidence of leptospirosis showed the distribution  of leptospirosis cases tend to be  concentrated in Sampang district which  had a history of flooding  status.  The conclusion is rainfall, altitude, and presence of flood are risk factors  of leptospirosis. The advice is to improve  surveillance of patients  with leptospirosis particularly during floods,  to do outreach to the community, to perform cross-sector cooperation, to avoid or to reduce the frequency of direct contact with the flood to minimize  transmission of leptospirosis.Keywords: leptospirosis incidence, risk factors,  mapping